Establishing the Language Center in the Context of Teaching Foreign Languages in Ukraine in the 1930s - Matsko, Dmytro (Pedagogical Discourse, 2013)
The article deals with the problem of teaching foreign languages in Ukraine in the 1930s. The process of establishing tight contacts with foreign countries is highlighted. The analysis of archive sources proves the necessity to systemize and improve the process of teaching foreign languages. The improvement is considered to lie in establishing the Language Center which has to govern the system of language education in Ukraine. Studying the archive materials enables to determine the tasks of the center in the context of teaching foreign languages in Ukraine in the 1930s.